An unexpected discovery of a novel potentially pathogenic APP gene variant: a case report of slowly progressive Alzheimer’s disease with prominent cerebral amyloid angiopathy - Sykora, Matyas; Harmackova, Marie; Parobkova, Eva; Rusina, Robert; Matěj, Radoslav (Frontiers in Neuroscience, 2026)
Amyloid precursor protein (APP) plays an essential role in brain function and development. Variants in the APP gene are associated with both familial Alzheimer’s disease and cerebral amyloid angiopathy. We report a case of early onset, slowly progressive mixed dementia with a newly identified APP variant. The patient developed mild cognitive impairment at age 51, followed by neuropsychiatric symptoms, seizures, and progressive white matter changes. Despite a fluctuating clinical course, significant deterioration occurred later, culminating in death at age 77. Genetic testing revealed an APP c.2086G > A (p.Gly696Ser) variant, currently classified as a variant of uncertain significance (VUS). Postmortem examination showed definite AD neuropathologic changes, with fully blown amyloid pathology including amyloid deposits in plaques as well as in severe generalized cerebral angiopathy with concomitant advanced FTLD-tau pathology. In silico analysis of the variant’s impact was performed, and the inconclusive results are discussed later.